Evaluation of 1‐dimensional nanomaterials release during electrospinning and thermogravimetric analysis. (25th June 2021) - Daneshvar, Farhad; Hankin, Steve; Fern, Gordon; Chen, Hengxi; Zhang, Tan; Aitken, Rob; Sue, Hung‐Jue
Abstract: The growing research interests with engineered nanomaterials in academic laboratories and manufacturing facilities pose potential safety risks to students and workers. New nanoparticle substances, compositions, and processing approaches are developed regularly, creating new health risks which may not have been addressed previously. Accordingly, the Institute of Occupational Medicine conducted field studies at Texas A&M University (TAMU) to characterize possible particle emissions during processing and fabrication of carbon nanotubes, copper nanowires, and polymeric fibers. The nature of the monitoring work carried out at TAMU was to investigate the potential release of 1D nanomaterials to air from activities associated with synthesis, handling, thermal gravimetric analysis, and electrospinning processes, and evaluate the effectiveness of the utilized control measures. The potential nanoparticle release to air from each activity was investigated using a combination of particle detection instrumentations, coupled with standard filter‐based sampling techniques. The analyses indicated that a measurable quantity of free carbon nanosphere aggregates was detected during these activities; however, no free MWCNTs or nanowires were detected. Scanning electron microscopy identified the presence of carbon nanospheres aggregates on the filters. While the control measures used at TAMU are effective in containing the nanomaterial release during processing, poor handling and occupational hygiene practices can increase the risk of employee exposure to the nanomaterials.